2011
DOI: 10.1111/j.1708-8240.2011.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Desensitizing Agents on the Shear Bond Strength of Adhesive Resin Cement to Dentin

Abstract: The type of desensitizer used is an important factor regarding the bond strength of adhesive resin cements to dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
(98 reference statements)
1
11
1
Order By: Relevance
“…41 In contrast to the findings of this study, it was observed that Admira Protect increased the bond strength of resin cements. 41 Potassium fluoride reacts with the dentinal fluid and causes precipitation of calcium ions and proteins in the dentinal fluid that block the tubules. 42 SEM findings and mean bond strength values of this study same line with present study.…”
Section: Discussioncontrasting
confidence: 99%
“…41 In contrast to the findings of this study, it was observed that Admira Protect increased the bond strength of resin cements. 41 Potassium fluoride reacts with the dentinal fluid and causes precipitation of calcium ions and proteins in the dentinal fluid that block the tubules. 42 SEM findings and mean bond strength values of this study same line with present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown that the application of fluoride desensitizers did not affect the bond strength of self-etch adhesive systems to demineralized dentin, in agreement with the results found in the present study, although an etch-and-rinse adhesive system was used [29]. On the other hand, recent studies have shown a reduction in bond strength of adhesives to sound dentin after desensitization protocols, but this is inversely related to the fluoride concentration in the compound, because higher concentrations reduce the bond strength due to crystals precipitating on the dentin surface [30,31]. Moreover, bond strength was not affected in the groups containing fluoride as desensitizer due to the concentrations being relatively low: 2% in Desensibilize KF2%, 0.25% in Ultra EZ and 0.9% in Nano P.…”
Section: Discussionsupporting
confidence: 90%
“…9,17 However, none of the fillings were lost, probably due to the use of a cavosurface bevel. 18 The reduction in sensitivity may have been the result of the effect of potassium nitrate on nervous excitability.…”
Section: Discussionmentioning
confidence: 99%